Mathematical Modelling of Bonded Marine Hoses for Single Point Mooring (SPM) Systems, with Catenary Anchor Leg Mooring (CALM) Buoy Application—A Review - Chiemela Victor Amaechi; Facheng Wang; Jianqiao Ye (Journal of Marine Science and Engineering, 2021)
The application of mathematical analysis has been an essential tool applied on Catenary Anchor Leg Mooring (CALM) buoys, Wave Energy Converters (WEC), point absorber buoys, and various single point mooring (SPM) systems. This enables having mathematical models for bonded marine hoses on SPM systems with application with CALM buoys, which are obviously a requisite for the techno-economic design and operation of these floating structures. Hose models (HM) and mooring models (MM) are utilized on a variety of applications such as SPARs, Semisubmersibles, WECs and CALM buoys. CALM buoys are an application of SPM systems. The goal of this review is to address the subject of marine hoses from mathematical modeling and operational views. To correctly reproduce the behavior of bonded marine hoses, including nonlinear dynamics, and to study their performance, accurate mathematical models are required. The paper gives an overview of the statics and dynamics of offshore/marine hoses. The reviews on marine hose behavior are conducted based on theoretical, numerical, and experimental investigations. The review also covers challenges encountered in hose installation, connection, and hang-off operations. State-of-the-art, developments and recent innovations in mooring applications for SURP (subsea umbilicals, risers, and pipelines) are presented. Finally, this study details the relevant materials that are utilized in hoses and mooring implementations. Some conclusions and recommendations are presented based on this review.